Influence of ethical work climate, and ethical leadership on organizational performance and mediating role of organizational trust among employees in Malaysian SMEs - Khademfar, Mohammad (2015)
This study attempted to determine the influence of Ethical Work Climate (EWC) and Ethical Leadership (EL) on Organizational Performance (OP) in Small & Medium Malaysian Enterprises, which involve in electrical and electronic activities. Moreover, it examined the mediating role of Organizational Trust (OT) towards the OP. The study attempted to highlight the importance of OP which could be improved by organizations via EWC factors. In addition the influence of EL factors including Leader honesty, Interactional fairness, and Satisfaction with managers were also considered. The relationships between the independent variables (IV) including EWC, EL, and also contribution of OT as mediator towards the OP as dependent variable (DV) have been explained. According to official updated website of Malaysian Small and Medium Enterprises (SMEs), the total number of active established electrical and electronic SME is 1457 (SME CORP; Malaysia Official Website; 2013). The majority of these companies are located in, Selangor (36.2 percent), Kuala Lumpur (17.4 percent) Penang (16 percent), and Johor (16 Percent). The researcher chose the four major states mentioned above which contain the majority of companies (85.8 percent). The total number of SMEs in these four states is 1250, and they are located different areas of country. The respondents were top level managers, senior managers, middle managers (supervisor), support staff and ordinary workers who are working in electrical and electronic SMEs. The research design was descriptive and inferential using Structural Equation Modeling (SEM) method. Data were collected employing two types of questionnaires. The study utilized simple random sampling technique and 304 active companies selected randomly through an alphabetically organized name list. The study examined the perceived ethical climate that relates to organizational performance in Malaysian SMEs. To achieve this goal, Victor and Cullen's 36-item survey is used to find out the perceptions of top managers, senior managers and middle managers in organization; this typology of respondents is relevant (Mathews, 1998).. The style and level of exist- ethical climate has been measured by analyzing the mean Likert-type scale scores computed for individual responses based on the nine commonly observed in ethical climate literature (Cullen et al., 1993). High performance Organization model employed to design the instrument for dependent variable. Organizational Trust Index and Ethical leadership questionnaire provided with logic and acceptable reliability. In a pilot survey; 30 companies were selected to conduct survey. The reliability of instruments has been determined by measuring the Cronbach alpha. The value of Cronbach Alpha for all factors was above 0.70 which assumed the scale of measurement is reliable (Jacobs & Razavieh, 2005). The study relied on a face to face meeting and administering the questionnaire to respondents. Data were collected using a self-administered questionnaire distributed among 304 SMEs. Two sets of questionnaires were handed, set "A" was for the managers and set "B" was filled by one of employee in company. This specification of instrument related to the nature of variables. An initial period of a week was provided for each of the chosen SME to respond. A phone call was made after the week was up and a time was arranged for questionnaire pick-up. The results showed EWC and ELB, have significant influence on organizational performance. So all hypothesis positively confirmed through the results. Social learning theory (Bandura’s, 1977) that employed in current study explains the link among these three major variables and affirms the importance of managers’ role to enhance the performance in Malaysian enterprises. This is a new complex model that illustrates the relationship of appropriate variables within EC and OP. since the result shows the positive significant relationships, it means managers are role model and employees learn desired behaviors by observing how managers act. In addition it shows that manager’s fair employment of rewards and punishment can lead towards organization performance. The findings of this study provided insights into the effectiveness of EWC, EL, and the role of OT on O-P. In addition, it is important for organizations to build plans and strategies in terms of training programs, managing the leadership style, reward and punishment system. Meanwhile there is a need to highlight the importance of organizational interest elements such as ethical conduct, climate and trust as part of organizational development. Policies and training that places prominence on ethical conduct can be beneficial for the organization particularly those operating as smallmedium enterprises involved in manufacturing.